Proveniência sedimentar e ambientes tectônicos do Grupo Araxá em sua área tipo baseado em dados U-Pb de zircões detríticos, Sm-Nd e 87Sr/86Sr Implicações para a evolução da porção meridional do Orógeno Brasilia durante o Neoproterozóico - Andre Falci Cardoso (2016)
The southern portion of the Brasilia Orogen in central Brazil is characterized by an east-verging sequence of stacked nappes that causes the thrusting of metasedimentary rocks of different provenance, age and metamorphism upon one another. In this work, we focus on the metasedimentary rocks of the Araxá Group of the homonymous nappe. We present new detrital zircon U-Pb, whole-rock Sm-Nd and 87Sr/86Sr data of the Araxá Group in its type area, near the town of Araxá, where it has been defined. The samples from the external Araxá nappe which are close to the cratonic border yielded almost exclusevely craton-derived zircons, with the main peaks in between 1.0 and 2.5 Ga, TDM model ages between 1.8 and 2.0 Ga and 87Sr/86Sr between 0.7 and 0.9. Those results are similar for those found for the Canastra Group, which is commonly interpreted as part of the São Francisco paleocontinent western passive margin. However, samples collected progressively towards West in the Araxá nappe, towards the central part of the Brasília Orogen, yielded minor peaks at around 790 Ma, and a major Neoproterozoic peak of ca. 650 Ma in the most northwestern sample. The latter is very similar to the Neoproterozoic peak found in previews works in samples also mapped as Araxá Group in Goías state, about 500km northwest. One sample show a TDM of 1.4 Ga, very different from the others, suggesting influence of Neoproterozoic sources towards the West, within the orogenic region. This is representative of an important provenance shift recorded in the metasedimentary rocks of the Araxá nappe, with the lower and easternmost rocks representing part of the passive margin of the western São Francisco paleocontinent border (a distal correlative of the Canastra Group), with provenace mainly from this paleocontinent; and the upper and westernmost rocks representing slices of syn-orogenic sedimentary rocks with a predominant Neoproterozoic source related to magmatics arcs of the inner portion of the Brasilia Orogen interleaved with the former in a tectonic mélange. Our data also suggests that what is today mapped as Araxá Group throughout the states of Minas Gerais and Goiás actually represents a collective of intrincately tectonically interleaved schistose metasedimentary units of distinct provenance, age and tectonic setting, probably developed during different moments in the evolution of the Brasília Orogen, and thrusted upon one another during the final stages of the Brasilian Orogeny. Separating those units that show similar lithological contents, but distinct provenance and tectonic setting, is an important effort in the understanding of the Brasília Orogen evolution and of the amalgamation of West Gondwana in the central South American platform.